Del Pino, Julio A. (2015). Estructuras residenciales y movilidad. Más allá de la segunda residencia - Julián López-Colás (Documents d'Anàlisi Geogràfica, 2016)
Del Pino, Julio A. (2015) Estructuras residenciales y movilidad. Más allá de la segunda residencia Madrid: CIS, 381 p. ISBN 978-84-7476-666-0